Understanding the Factors of Adult Learners Dropping Out of E-learning Courses - Ju Sung Jun (Adult Education Research Conference, 2004)
The purpose of this study is to determine the specific set of variables that can best predict the reasons that adults dropout of workplace e-learning courses. A model including the predictors of attention, relevance, confidence, marital status, number of learning hours for the course, mandatory/voluntary attendance, and hours worked per week fits well (• 2 = 75.918, df = 7, and p < .000).